OVERLOAD AND SATISFACTION OF FAMILY MEMBERS OF PATIENTS WITH SCHIZOPHRENIA - Marcos Hirata Soares; Adriano Luiz da Costa Farinasso; Cristiane de Souza Gonçalves; Fernanda Pâmela Machado; Layla Karina Ferrari Ramos Mariano; Caroline Dominique dos Santos (Universidade Federal do Paraná, 2019)
Objective: To assess psychosocial care from the perspective of family members of schizophrenic patients. Method: A correlational study with 40 family members at a Psychosocial Care Center III of Londrina, Paraná, was conducted in 2015 and 2016. Variables related to the sociodemographic characterization and evaluation scales of the overload and satisfaction of the family members were obtained. Data were analyzed with measures of central tendency and correlation.Results: 24 caregivers were women, 23 were married, and the mean age was 46 years. The mean rate of satisfaction was 4.37, the overall mean value for objective overload was 2.26, and the overall mean value for subjective overload was 2.09. Conclusion: Although the family members were very satisfied, differences in overload scores revealed that they received good psychoeducational support, but the overload generated by their concern for their family member was the aspect that generated the highest levels of suffering. Such results may guide nurses to give directions to family members, to support then and reduce their overload.